Efektifitas Nigella Sativa Oil Untuk Mencegah Terjadinya Ulkus Dekubitus Pada Pasien Tirah Baring Lama - Utomo, Wasisto; Dewi, Yulia Irvani; Abdurrasyid, T. (Fakultas Keperawatan, Universitas Riau, 2012)
The study aims to determine the effectiveness of Nigella sativa oil to prevent decubitus ulcers in bedridden patients. Quasi-Experimental research design used to test the approach Randomized Post Only Control Design is divided into an interventiongroup and a control group. The study was conducted on clients who have not yet experienced bedrest and decubitus ulcers inhospitals Arifin Achmad Pekanbaru. Total sample 30 people, each group of 15 people by purposive sampling technique.Measurement tools such as observation sheets Pressure Ulcer Data Collecting Form with modifications. In the interventiongroup were given preferential treatment in the form of application of approximately 20 ml of Nigella sativa oil on the bony part1 time a day for 7 days. Analysis of univariate and bivariate data with Mann-Whitney test. The results showed a difference inmean scores decubitus ulcers significantly between the experimental group and the control group p value = 0.000 (p <0.05).Nigella sativa Oil can be applied in bedridden patients in the hospital.Keywords: Nigella sativa Oil, pressure ulcer, bedridden